The Influence of Audit Tenure and Audit Committee on Earnings Quality - Fatima Zakiya Razani; Liu Xia (Faculty of Economics and Business, Jenderal Soedirman University, 2017)
One of the Auditor and Audit committee role is to ensure the quality of corporate financial reporting process. This study aims to test the effect of the length of auditor tenure and audit committee on earning quality measured by the absolute value of discretionary accruals. A sample of 465 companies has been selected and data covering the period 2009-2014 has been collected from these firms, where 2325 observation were used in this analysis. The data collected form CSMAR and analyzed using GLS regression analysis. This study found that the short audit tenure on Chinese listed company in Shenzhen Stock Exchange has a significance negative influence on earning quality, meanwhile this study found that audit committee which is measure by the size of the committee does not has a significance influence on earning quality. This study suggests that auditor should have a longer tenure to gain adequate knowledge of client’s business. Moreover companies should strengthen the role of their audit committee in monitoring financial reporting process by improved their activity and financial knowledge of the member.